2020
DOI: 10.1016/j.jenvman.2020.110819
|View full text |Cite
|
Sign up to set email alerts
|

Linkage analysis of economic consumption, pollutant emissions and concentrations based on a city-level multi-regional input–output (MRIO) model and atmospheric transport

Abstract: China is experiencing serious atmospheric pollution, which also exhibits significant spatial heterogeneity. The Chinese government has implemented targeted pollution control measures at the city level, emphasizing coordination among cities to prevent and control air pollution in key regions such as Beijing-Tianjin-Hebei (BTH) urban agglomeration. This study combined an inter-city multi-regional input-output (MRIO) model with an air quality dispersion model consisting of a weather research and forecasting (WRF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Initially, a correlation analysis is required in DEA to reach reliable results (Kao & Liu, 2021; Wang, Li, et al, 2020) If an input is observed to be in a low correlation with all of the outputs, that input is considered to be not significant for the model and can be omitted (Yang, 2009). In correlation analysis, it is preferred that the effects of inputs on outputs are in the same direction.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, a correlation analysis is required in DEA to reach reliable results (Kao & Liu, 2021; Wang, Li, et al, 2020) If an input is observed to be in a low correlation with all of the outputs, that input is considered to be not significant for the model and can be omitted (Yang, 2009). In correlation analysis, it is preferred that the effects of inputs on outputs are in the same direction.…”
Section: Resultsmentioning
confidence: 99%
“…The MRIO model, which elucidates the mutual interrelation among sectors or regions from the perspective of supply chain, is a prevalent approach for investigating energy [35,36], water [37,38], CO2 emissions [39,40], and other pollutant emissions [41][42][43] embedded within interregional trade. Consistent with Qian et al [16], this study first esti- The MRIO model, which elucidates the mutual interrelation among sectors or regions from the perspective of supply chain, is a prevalent approach for investigating energy [35,36], water [37,38], CO 2 emissions [39,40], and other pollutant emissions [41][42][43] embedded within interregional trade. Consistent with Qian et al [16], this study first estimated the SO 2 emissions attributable to production, consumption, and income using the MRIO model.…”
Section: Multi-regional Input-output (Mrio) Analysismentioning
confidence: 99%
“…To evaluate inter-city economic consumption, pollutant emission, and concentration among 13 cities in the Beijing-Tianjin-Hebei (BTH) urban agglomeration, this study combines an inter-city multi-regional input-output (MRIO) model with an air quality dispersion model consisting of a weather research and forecasting (WRF) model and the CALPUFF model (WRF/CALPUFF) (Wang et al, 2020). As an example, NOx is used.…”
Section: Sustainability and Manufacturingmentioning
confidence: 99%